Mass transfer of proteins in aqueous two-phase systems - Kaplanow, Irene; Görzgen, Fabian; Merz, Juliane; Schembecker, Gerhard (Technische Universität Dortmund, 2019)
Aqueous Two-Phase Extraction is known to be a gentle separation technique for biochemical molecules where product partitioning is fast. However, the reason for the high mass transfer rates has not been investigated, yet. Many researchers claim that the low interfacial tension facilitates the formation of very small droplets and with it a large interfacial area causing a fast partitioning. However, an experimental evidence for this hypothesis has not been published yet. In this study, the mass transfer coefficients of two proteins, namely lysozyme and bromelain, were determined by providing a defined interfacial area for partitioning. Compared to low molecular weight solutes the mass transfer coefficient for the proteins investigated was small proving for the first time that the large interfacial area and not fast diffusion seems to be the reason for fast protein partitioning.
Keywords: 660; Extraktion